2013
DOI: 10.1099/vir.0.054049-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and histological variation in avipoxviruses isolated in South Africa

Abstract: Thirteen novel avipoxviruses were isolated from birds from different regions of South Africa. These viruses could be divided into six groups, according to gross pathology and pock appearance on chick chorioallantoic membranes (CAMs). Histopathology revealed distinct differences in epidermal and mesodermal cell proliferation, as well as immune cell infiltration, caused by the different avipoxviruses, even within groups of viruses causing similar CAM gross pathology. In order to determine the genetic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 51 publications
(109 reference statements)
5
52
1
Order By: Relevance
“…Classically, APV are considered to be host species or order specific and taxonomy was based on this concept. This has been recently questioned by many authors [4][5][6]23] since some taxa like Columbidae and Accipitridae can be infected by a wide diversity of strains, however with different sensitivity depending on the virus involved. This apparent diversity could be explained by some infections occurring as accidental events, especially in zoological collections where many species are housed closely, and it is suggested that such an infection could not lead to sustainable epornitics [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classically, APV are considered to be host species or order specific and taxonomy was based on this concept. This has been recently questioned by many authors [4][5][6]23] since some taxa like Columbidae and Accipitridae can be infected by a wide diversity of strains, however with different sensitivity depending on the virus involved. This apparent diversity could be explained by some infections occurring as accidental events, especially in zoological collections where many species are housed closely, and it is suggested that such an infection could not lead to sustainable epornitics [23].…”
Section: Discussionmentioning
confidence: 99%
“…The complete fpv140 gene sequence (933-1020 bp) was used to build an NJ tree ( Figure 2). Its analysis provided the clades/subclades classification as previously described for clade A [4,5] …”
Section: Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…16 Loci H3L and fpv175-176 have also been used for phylogenetic classification of avipoxviruses. 15 In this study we found that a better discrimination of the isolates can be achieved performing the phylogenetic analysis with a cnpv186-187 concatenated fragment including the 59 end of cnpv186 and the 39 end of cnpv187, instead of the cnpv186 gene alone indicated by Pawar et al 17 Based in this partial encoding sequence, in contrast to the P4b fragment, it was possible to observe a better relationship between the isolates and their host species. The blast analysis revealed that this fragment is more variable than the P4b-encoding sequence, since maximum variability reached 43% in the cnpv186-187 nucleotide sequence and 28% in the P4b-encoding gene.…”
Section: Phylogenetic Analysismentioning
confidence: 75%
“…There are currently seven subclades within clade A and four subclades within clade B. 5,15 Since one representative of each subclade was included in this analysis, all subclades, A1 to A7 and B1 to B4, are represented and can be identified in the tree (Fig. 4), confirming the findings of Le Loc et al 5 For the phylogenetic analysis based on cnpv186-187 region, the intergenic region was removed, since this noncoding region could have impact on large-scale phylogenetic inference.…”
Section: Phylogenetic Analysismentioning
confidence: 99%